Responsabilidad penal por incendios forestales en el cantón Chilla, periodo 2013-2014. - Chuchuca Chuchuca, Jaime Rodrigo; Guartatanga Jadán, José Ruperto; Narváez Yaguarcos, Wilson César (Machala : Universidad Técnica de Machala, 2015)
La constitución de la República del Ecuador protege los derechos de la sociedad en general, y además de manera responsable se le ha brindado protección de manera inmediata a la naturaleza, concediéndoles derechos. Todo esto obviamente para la protección del ecosistema dentro del cual nos enmarcamos los ecuatorianos. La protección a la naturaleza se la realiza de manera directa ya sea mediante acciones de protecciones o mediante acciones preventivas de autoridades administrativas y de control. Pero cuando la vulneración ya se ha ocasionado como en el caso de los incendios forestales, tenemos el Código Orgánico Integral Penal para establecer las anti conductas, el procedimiento y las sanciones a las que se les deben someter a los responsables de dichos actos incendiarios. El delito de incendio forestal no es una invención reciente de los legisladores, pues su antecedente ya lo encontramos en códigos y leyes antiguas y cuyas sanciones eran drásticas que en algunos casos se penaba con la quema de la persona que provocaba tales incendios. Algunos pueblos lo tipificaban para proteger las propiedades agrícolas, que en aquellos tiempos era la actividad principal del hombre, y de ahí quizás se pudiera comprender la dureza de las sanciones en algunos lares del antiguo mundo. Largo recorrido ha tenido que transitar la tipificación penal del incendio forestal para que los duros castigos de antaño sean minimizados a penas de prisión no tan graves, y claro ello se debe a que quizás la agricultura ya no sea la actividad más importante del hombre, pues la diversidad de actividades del mundo contemporáneo, permite a su vez el establecimiento de penas según la necesidad de los bienes jurídicos que se quieren protege
The constitution of the Republic of Ecuador protects the right of society. Beside confers protection inmediatly to the nature granting it rights, Al this obviously for the protection of the ecosystem in which we are frame all the ecuadorians. The protection to the nature is completed in a direct way with actions of protections and preventive measures of administrative authority and control but when the infringement has been caused as in the case of forest fires , we have the organic penal integral code to establish the procedures and penalties which it should submit to the reponsable of those acts . The crime of wildfire is not a recent invention of legislators as its antecedent we found in ancient laws and codes and whose sanctions were drastic in some cases were sanctioned with the burning of the person who caused such fires. Some peoples typified to protect the agricultural properties that at the time was the main activity of man and hence perhaps it could understand the harshness of penalties in some places of the ancient world. Long time had to move the criminal typification of wildfire for harsh punishments of yesteryear are minimized to less penalties prison and perhaps it is because agriculture is no longer the most important activity of the man. Since the diversity of activities of today's world turn allows the establishment of penalties according to the need of legal properties to be protected.The constitution of the Republic of Ecuador protects the right of society. Beside confers protection inmediatly to the nature granting it rights, Al this obviously for the protection of the ecosystem in which we are frame all the ecuadorians. The protection to the nature is completed in a direct way with actions of protections and preventive measures of administrative authority and control but when the infringement has been caused as in the case of forest fires , we have the organic penal integral code to establish the procedures and penalties which it should submit to the reponsable of those acts . The crime of wildfire is not a recent invention of legislators as its antecedent we found in ancient laws and codes and whose sanctions were drastic in some cases were sanctioned with the burning of the person who caused such fires. Some peoples typified to protect the agricultural properties that at the time was the main activity of man and hence perhaps it could understand the harshness of penalties in some places of the ancient world. Long time had to move the criminal typification of wildfire for harsh punishments of yesteryear are minimized to less penalties prison and perhaps it is because agriculture is no longer the most important activity of the man. Since the diversity of activities of today's world turn allows the establishment of penalties according to the need of legal properties to be protected.
Keywords: PENAL; INCENDIO; FORESTAL; CHILLA